2021
DOI: 10.12659/msm.934949
|View full text |Cite
|
Sign up to set email alerts
|

Editorial: A Decline in Influenza During the COVID-19 Pandemic and the Emergence of Potential Epidemic and Pandemic Influenza Viruses

Abstract: There have been five viral pandemics in the past century, four were due to influenza, and the ongoing COVID-19 pandemic is due to SARS-CoV-2 infection. During the COVID-19 pandemic, there has been a 99% global reduction in the diagnosis of influenza. Also, from 2020, global mortality rates from influenza fell to record levels during the influenza seasons in the southern and northern hemispheres. However, as social restrictions become lifted and the winter season begins in the northern hemisphere, it is expecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Several studies conducted during the early months of the pandemic demonstrated an overall decline in non-COVID-19 respiratory viral infections [ 24 , 25 ]. Reports from other countries, including China, Australia, and France, also cited diminished flu cases since the pandemic was declared [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies conducted during the early months of the pandemic demonstrated an overall decline in non-COVID-19 respiratory viral infections [ 24 , 25 ]. Reports from other countries, including China, Australia, and France, also cited diminished flu cases since the pandemic was declared [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although nonpharmaceutical interventions helped to reduce non-COVID-19 respiratory viral diseases, we should not shift our focus from traditional respiratory viruses to COVID-19 only. The upsurge of RSV perhaps was not an isolated phenomenon and should be considered as an eye-opener as other respiratory viruses can have a similar comeback [ 25 ]. Some experts have even warned against the future resurgence of flu [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…These declines have been broadly attributed to population-wide preventative measures, including handwashing, face mask wearing and social distancing. Previous to COVID-19, significant events that restrict human mobility, such as major winter storms, have shown reductions in transmission of influenza as well as other respiratory infections [ 36 ] Preventative measures such as mask wearing and social distancing have become and remain important mitigation measures for reducing transmission of SARS-CoV-2 [ 37 ], and growing evidence suggests these may have a greater impact on reducing the spread of influenza [ 38 , 39 ], RSV, AdV and other respiratory infections even in warmer climates.…”
Section: Discussionmentioning
confidence: 99%
“…From 2020 and during the COVID-19 pandemic, several important epidemiological trends in influenza A infections have occurred. Between the influenza seasons from October 2020 to July 2021 in both the northern and southern hemispheres, mortality rates from influenza fell dramatically [ 3 , 4 ]. During the COVID-19 pandemic, resources were directed toward monitoring and disease surveillance for SARS-CoV-2 infections, which raised concerns that undetected strains of influenza, including highly pathogenic avian influenza (HPAI), might result in an influenza pandemic [ 4 , 5 ].…”
mentioning
confidence: 99%